2023
DOI: 10.1002/ett.4794
|View full text |Cite
|
Sign up to set email alerts
|

Joint resource allocation and power allocation scheme forMIMOassistedNOMAsystem

Abstract: Multiple input multiple output (MIMO) plays an integral role in improving energy efficiency for enhancing all users' quality of service (QoS). For 5G wireless communication (WC), the NOMA strategy is used with the MIMO system to improve the system's sum rate and computational complexity. In this, terahertz (THz) band communication is introduced for future demand to carry more users and obtains high multiplexing gain. Multiple antenna arrays are used in the MIMO‐NOMA system to achieve high signal transmission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This is because the energy is shared between multiple users of the same beam. Therefore, a lot of research has been revealed to study the energy allocation of NOMA-MIMO see for example the references, [17], [19][20][21][22]. The formula for optimizing the QoS with power-allocation constraint can be written as follows, The optimization expression in ( 9) aims to attain a fair quality of service (i.e., best QoS) among all the users, "𝑅 𝑡ℎ = 𝐦𝐢𝐧 𝑘 ln( 1 + Γ 𝑘𝑖 )" denotes the minimum amount of data that each user should have, or in other words, it represents the QoS to confirm the user's fairness performance, Γ 𝑘𝑖 refers to SINR, and 𝑃 𝑡 stands for the total power transmitted by the whole system.…”
Section: Qos-balance Problem Formulationmentioning
confidence: 99%
“…This is because the energy is shared between multiple users of the same beam. Therefore, a lot of research has been revealed to study the energy allocation of NOMA-MIMO see for example the references, [17], [19][20][21][22]. The formula for optimizing the QoS with power-allocation constraint can be written as follows, The optimization expression in ( 9) aims to attain a fair quality of service (i.e., best QoS) among all the users, "𝑅 𝑡ℎ = 𝐦𝐢𝐧 𝑘 ln( 1 + Γ 𝑘𝑖 )" denotes the minimum amount of data that each user should have, or in other words, it represents the QoS to confirm the user's fairness performance, Γ 𝑘𝑖 refers to SINR, and 𝑃 𝑡 stands for the total power transmitted by the whole system.…”
Section: Qos-balance Problem Formulationmentioning
confidence: 99%